The validity of the principle of mutual trust between the EU Member States in mutual assistance for the recovery of public claims - Olszanowski, Jan; Piątek, Wojciech (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The cooperation between the EU Member States for the recovery of public claims has been gradually strengthened through expanding the subjective scope to new categories of public claims, establishing forms of cooperation, most notably the possibility to recover claims arising in one state by authorities of another state, and establishing separate institutional frameworks of cooperation. The EU legislature placed great emphasis on the most transparent development of relationships between the EU Member States, and thus the validity of the principle of trust. The article analyses the current international cooperation in the recovery of public claims in view of the principle of mutual trust between the Member States that forms the basis for such cooperation.